Ion-electrostatic component of surface forces when particles interact within electrolyte - Grechko, L. G.; Grischuk, E. Yu.; Lerman, L. B.; Pokotilo, O. Ya. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2006)
A solution has been constructed of the Debye-Huckel equation for system spheres with arbitrary radii and surface charges or potentials in electrolyte solutions. A general theoretical method for description of inter-particle interaction within such systems has been elaborated. The practically important case of two spheres has been considered in detail. Finite closed formulae to calculation of interaction energy of two spherical particles with constant surface charges have been obtained from general expressions within zero approximation. The known relationships of Deryagin-Landaw-Lifshits-Overbeek theory follow from our formulae in the limit cases.